Karakteristik Dispensasi Kawin di Pengadilan Agama Ambarawa Tahun 2022: Characteristics of Marriage Dispensation in Ambarawa Religious Court in 2022 - Feny Marselina; Eti Salafas (Journal of Holistics and Health Sciences (JHHS), 2023)
The rate of child marriage in Indonesia is ranked 7th (UNICEF, 2018) and ranked 2nd in ASEAN with a child marriage rate of 27.6 percent or around 23 million children married in Indonesia in 2018 (KPPPA, 2018), the Central Java Women's Empowerment and Child Protection Office recorded an increase in child marriage. In 2019, there were 2,049 child marriages until September 2020, an increase of 8,338 cases. This figure places Semarang Regency in 26th rank out of 35 regencies/cities in Central Java Meanwhile, in the first quarter of 2022, there were 63 cases. In 2021 there were 216 because these 63 cases were still in the first quarter of 2022. Marriage dispensation is granted by the Religious Court to prospective brides aged less than 19 years (men) and 16 years (women). In the Ambarawa Religious Court in 2022, there were 231 cases of marriage dispensation verdicts. This study aims to describe the characteristics of marriage dispensation in the Ambarawa Religious Court area. This study is quantitative descriptive with a cross sectional approach using secondary data on marriage dispensation application documents from the Ambarawa religious court. The population is juvenile couples who applied for marriage dispensation at the Ambarawa Religious Court with 231 complete documents. Univariate analysis uses frequency distributions. The results of the study, the majority of couples' education is junior high school with the percentage of women (63.6) more than men (44.2%). Men's income is mostly (65.8%) more than UMR while women's income is almost entirely below UMR (94.4%), the reason for applying for marriage dispensation is most of them getting pregnant out of wedlock (19.9%). It is hoped that there will be efforts to increase knowledge, attitudes and positive social behavior of adolescents in order to avoid the occurrence of pregnancy out of wedlock.   ABSTRAK Angka pernikahan anak di Indonesia berada di peringkat 7 (UNICEF, 2018) dan peringkat 2 ASEAN dengan angka pernikahan usia anak 27,6 persen atau sekitar 23 juta anak yang menikah di Indonesia tahun 2018 (KPPPA, 2018), Dinas Pemberdayaan Perempuan dan Perlindungan Anak Jawa Tengah mencatat adanya peningkatan pernikahan anak di bawah umur. Pada tahun 2019 ada 2.049 pernikahan anak hingga September 2020 jumlahnya meningkat 8.338 kasus. Angka tersebut menempatkan Kabupaten Semarang pada peringkat 26 dari 35 kabupaten/kota di Jawa Tengah. Sedangkan pada triwulan pertama 2022, terjadi 63 kasus. Pada 2021 terdapat 216 karena 63 kasus ini masih periode triwulan pertama pada tahun 2022. Dispensasi kawin diberikan oleh Pengadilan Agama kepada calon mempelai usia kurang 19 tahun (pria) tahun dan 16 tahun (wanita). Di Pengadilan Agama Ambarawa pada tahun 2022 ada 231 perkara putusan dipensasi kawin. Penelitian ini bertujuan  mengambarkan karakteristik dispensasi kawin di wilayah Pengadilan Agama Ambarawa. Penelitian ini Deskriptif kuantitatif dengan pendekatan cross sectional menggunakan data sekunder dokumen permohonan dispensasi kawin pengadilan agama Ambarawa. Populasinya adalah pasangan remaja yang mengajukan dispensasi kawin di Pengadilan Agama Ambarawa dengan dokumen lengkap sebanyak 231. Analisis univariat menggunakan distribusi frekuensi. Hasil penelitian, mayoritas pendidikan pasangan adalah SMP dengan persentase Perempuan (63,6) lebih banyak dari laki-laki (44,2%). Penghasilan laki-laki sebagian besar (65,8%) lebih dari UMR sedangkan penghasilan perempuan hampir seluruhnya dibawah UMR (94,4%), alasan pengajuan dispensasi kawin paling banyak adalah hamil diluar nikah (19,9%). Diharapkan ada upaya peningkatan pengetahuan, sikap dan perilaku pergaulan remaja yang positif supaya terhindar kejadian hamil diluar nikah.